SISTEM INFORMASI MANAJEMEN TRAINING MENGGUNAKAN METODE AGILE SOFTWARE DEVELOPMENT THE PAPANDAYAN HOTEL BANDUNG - Irman Hariman; Christina Meilisa (UNIVERSITAS KEBANGSAAN, 2020)
Abstract: Training / Training is one of the human resource development programs aimed at achieving competent and quality performance. Management Information System which is the application of information systems within the organization to gather some information needed by all levels of management and those who will need information. Training needs assessment is very important because it provides information about the level of expertise and knowledge of the organization's human resources. With this information, managers can find out the organization's needs and employee capabilities. One method used in this research is Agile Software Development, a type of short-term system development that requires rapid adaptation and development of changes in any form. Using the Dynamic System Development Method (DSDM) process model which is a rapid software development approach that